Distortion Performance of Underwater Acoustic Sensor Networks - Andrej Stefanov (International Journal of Distributed Sensor Networks)
The paper studies the distortion performance of multihop underwater acoustic sensor networks. The network is composed of bottom mounted sensor nodes and the sensor to sensor links experience Rician fading. The distortion is evaluated for the case when there is interference from other sensors in the network. The focus is on the sustainable number of hops in the network for a maximum allowed (target) route distortion requirement. Numerical examples are provided that illustrate the results of the analysis and the regions where the network operation is limited, namely, the coverage-limited region and the interference-limited region. The paper also considers the impact of retransmissions on the distortion performance. It is found that the network connectivity and robustness improve with automatic repeat request (ARQ). The improvements are manifested as a reduction of the regions of limited performance, that is, an increase of the region where the network exhibits full connectivity. The analysis results are illustrated through numerical examples.